Diagnosis of compression syndromes in neurological practice - Siutka, Dominik; Bonek, Katarzyna; Fudala, Malgorzata; Brola, Waldemar (Medical Studies/Studia Medyczne, 2019)
Compression syndromes are a multidisciplinary issue. Many specialists are involved in the problem of peripheral nerve injury, but it is the neurologist’s task to identify the nerve and locate the level of its damage. The nerve damage occurs in the anatomic isthmus and in the area of the nerves’ course under the surface of the skin. Compression syndromes manifest themselves with muscle weakness and sensory ailments such as paraesthesia, numbness, and pain. Symptoms occur in the sensory and motor supply of a given nerve. In diagnostics, we use clinical evaluation, provocative tests, electrophysiological diagnostics, and imaging examinations. Treatment is divided into conservative and operational. The increased availability of electrophysiological research in recent years allows for precise differential diagnosis of individual compression syndromes and the selection of optimal treatment. In this study, a clinical picture of the most frequent syndromes of compression syndromes and the role of electrophysiological research in their diagnosis and treatment are presented.